Accessibility of General Adult Education An Analysis of the Restructuring of Adult Education Governance in Denmark. Issue 1 (February 2022) - Rasmussen, Annette; Lolle, Elisabeth Lauridsen
The purpose of this paper is to examine how adult education institutions have developed in close connection with the Danish welfare state and how structural reforms since the 1990s have changed the institutional structure and impacted accessibility. This involves analyses of the main functions linked to the different types of adult education institutions (VUCs) in Denmark and their development in relation to welfare state policies in the first instance and to globalization and competition state policies in the second. Thus, the paper provides a historical outline of the development of adult education institutions in two main areas, a vocational and a general, followed by an analysis of selected policy documents on structural reforms. Focusing on the reforms of 2000, 2007, and 2018, the analysis identifies external and internal limitations to accessing general adult education. In conclusion, the market orientation of the VUC entails limitations to both external and internal accessibility.